Method of tubes pressing by electrical discharge and its particularities; Korus 2002 - Zhuchkov A. I. Zhuchkov Ivanovich; Kurets (Kuretz) V. I. Valery Isaakovich; Filatov G. P. Gennady Petrovich; Tarakanovsky E. N. Eduard Nikolaevich (2002, 2002)
Title screen